NADPH oxidase deficiency underlies dysfunction of aged CD8+ Tregs - Wen, Zhenke; Shimojima, Yasuhiro; Shirai, Tsuyoshi; Li, Yinyin; Ju, Jihang; Yang, Zhen; Tian, Lu; Goronzy, Jörg J.; Weyand, Cornelia M. (The Journal of Clinical Investigation, 2016)
Immune aging results in progressive loss of both protective immunity and T cell–mediated suppression, thereby conferring susceptibility to a combination of immunodeficiency and chronic inflammatory disease. Here, we determined that older individuals fail to generate immunosuppressive CD8+CCR7+ Tregs, a defect that is even more pronounced in the age-related vasculitic syndrome giant cell arteritis. In young, healthy individuals, CD8+CCR7+ Tregs are localized in T cell zones of secondary lymphoid organs, suppress activation and expansion of CD4 T cells by inhibiting the phosphorylation of membrane-proximal signaling molecules, and effectively inhibit proliferative expansion of CD4 T cells in vitro and in vivo. We identified deficiency of NADPH oxidase 2 (NOX2) as the molecular underpinning of CD8 Treg failure in the older individuals and in patients with giant cell arteritis. CD8 Tregs suppress by releasing exosomes that carry preassembled NOX2 membrane clusters and are taken up by CD4 T cells. Overexpression of NOX2 in aged CD8 Tregs promptly restored suppressive function. Together, our data support NOX2 as a critical component of the suppressive machinery of CD8 Tregs and suggest that repairing NOX2 deficiency in these cells may protect older individuals from tissue-destructive inflammatory disease, such as large-vessel vasculitis.